Female in top management and firm performance nexus: Empirical evidence from Ghana - Joseph Dery Nyeadi; Kofi Kamasa; Stephen Kpinpuo (Cogent Economics & Finance, 2021)
This study investigates empirically the link between females in top management and firm performance in Ghana. This study employs the Instrumental Variable (IV) Two Stage Least Squares (2SLS) technique of estimation in determining the impact of females in top management on firm performance using World Bank Enterprise Survey (WBES) data across 720 firms in Ghana. This technique is very robust as it has the power to control for any possible endogeneity bias, which can lead to spurious results. After controlling for reverse causality, our results reveal that the inclusion of females in top management impacts positively on firm performance in Ghana. We further note that though innovation has direct positive impact on firm performance, there is no evidence of any moderating roles played by innovation or education in the link between female in top management and firm performance in Ghana. The results of our study should however be interpreted with a bit of caution as we have not been able to examine the time dynamics of our findings due to lack of reliable panel data. Apart from serving as a reference literature for future studies, the study is very useful to both government and firms who make decisions in respect of females in management.
Keywords: 330; Female; firm performance; Ghana; instrumental variable; management